Efektivitas Metode Ceramah dalam Pembelajaran Filsafat Ilmu bagi Mahasiswa Baru di STAI Al-Andina Sukabumi - Dasep Hanan Mubarok; Neng Lailatul Faaizah; Aceng Supyan; Syifa Aqmaliyah; Muhammad Zaki (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study aims to describe the implementation of learning methods, assessment systems, and learning evaluation in the Philosophy of Science course at STAI Al-Andina Sukabumi, particularly for first-semester students. The research employed a qualitative approach with a descriptive design. Data were collected through semi-structured interviews with the course lecturer to explore the rationale for selecting the lecture method, assessment practices, and evaluation strategies applied in the learning process. The findings indicate that the lecture method combined with guided discussion was chosen as an adaptive strategy to help students develop a conceptual foundation for abstract and theoretical material. The assessment system places greater emphasis on student attendance and participation as a form of process-oriented assessment that encourages active engagement. Learning evaluation is conducted continuously through technology-based quizzes to monitor students’ understanding progressively. These results suggest that the Philosophy of Science learning process at STAI Al-Andina has adopted a contextual and formative pedagogical approach; however, further development of more varied assessment and evaluation methods is still needed to accommodate students’ diverse abilities.